Safety and practicality of an excisional lymph node study driving HIV cure research in South Africa - Khaba, Trevor; Papadopoulos, Andrea Olga; Nkosi, Thandeka; Nxele, Sifundo; Ngubane, Thandekile; Jajbhay, Ismail; Pansegrouw, Johan; Ndhlovu, Zaza M. (Frontiers in Immunology, 2024)
Studying diseased human tissues offers better insights into the intricate interactions between pathogens and the human host. In conditions such as HIV and cancers, where diseases primarily manifest in tissues, peripheral blood studies are limited in providing a thorough understanding of disease processes and localized immune responses. We describe a study designed to obtain excisional lymph nodes from volunteers for HIV reservoir studies. Since study commencement in 2015, 173 Lymph node excisions have been performed, resulting in collection of 159 lymph node tissues. Lymph nodes are surgically excised from study volunteers using a minimally invasive procedure, performed in a minor theater under local anesthesia. The surgery takes less than 30 minutes to complete, minimizing risk and stress on the volunteer. The small incision made during the procedure typically heals within a week. The associated discomfort is generally manageable, and participants are often able to resume their regular activities within a day. Only 5.7% of the study participants experienced minor adverse events, such as swelling and prolonged wound healing, recovering within 2 weeks with no serious adverse events reported. Our study demonstrates that when done with outmost care, obtaining excised lymph nodes for research is relatively safe and practical.